A storyline approach: integrating comprehensive, interdisciplinary research results to create narratives – in the context of the net-zero target in Germany - Köhnke, Fiona; Steuri, Bettina; Baetcke, Lars; Borchers, Malgorzata; Brinkmann, Torsten; Dittmeyer, Roland; Dornheim, Martin; El Zohbi, Juliane; Förster, Johannes; Gawel, Erik; Görl, Knut; Herbst, Michael; et al. (Frontiers in Environmental Science, 2024)
With the amendment to the German Climate Change Act in 2021, the Federal Government of Germany has set the target to become greenhouse gas neutral by 2045. Reaching this ambitious target requires multisectoral efforts, which in turn calls for interdisciplinary collaboration: the Net-Zero-2050 project of the Helmholtz Climate Initiative serves as an example of successful, interdisciplinary collaboration with the aim of producing valuable recommendations for action to achieve net-zero CO2 emissions in Germany. To this end, we applied an interdisciplinary approach to combining comprehensive research results from ten German national research centers in the context of carbon neutrality in Germany. In this paper, we present our approach and the method behind the interdisciplinary storylines development, which enabled us to create a common framework between different carbon dioxide removal and avoidance methods and the bigger carbon neutrality context. Thus, the research findings are aggregated into narratives: the two complementary storylines focus on technologies for net-zero CO2 emissions and on different framing conditions for implementing net-zero CO2 measures. Moreover, we outline the Net-Zero-2050 results emerging from the two storylines by presenting the resulting narratives in the context of carbon neutrality in Germany. Aiming at creating insights into how complementary and related expertise can be combined in teams across disciplines, we conclude with the project’s lessons learned. This paper sheds light on how to facilitate cooperation between different science disciplines with the purpose of preparing joint research results that can be communicated to a specific audience. Additionally, it provides further evidence that interdisciplinary and diverse research teams are an essential factor for defining solution spaces for complex, interdisciplinary problems.